2022
DOI: 10.1088/1755-1315/1114/1/012066
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Russia-Ukrainian war on green energy financing in Europe

Abstract: The energy crisis started because of the war between Russia and Ukraine and European countries’ imposition of economic sanctions. Russia supplies 40% of gas and 25% of crude oil to most European countries. In retaliation for the sanctions, Russia required the purchase of its gas and oil in its ruble. However, this policy was rejected by European countries, resulting in reduced energy supply as the price of gas and oil rose. European countries are trying to reduce Russia’s energy dependence by looking for envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The Russia-Ukraine war has increased demand for CCS as a way to address greenhouse gas emissions and improve energy security. Governments and businesses are investing more in CCS research and development, and there is a growing momentum to deploy CCS technologies at scale [245].…”
Section: Accelerated Transition To a Low-carbon Economymentioning
confidence: 99%
“…The Russia-Ukraine war has increased demand for CCS as a way to address greenhouse gas emissions and improve energy security. Governments and businesses are investing more in CCS research and development, and there is a growing momentum to deploy CCS technologies at scale [245].…”
Section: Accelerated Transition To a Low-carbon Economymentioning
confidence: 99%
“…Regarding the progress towards renewable energy, the level of use and financing by European countries was found to be rising and exceeding the determined indicative renewable energy directive path. Almost all member states of the European Union experienced a significant increase in renewable energy consumption [128]. Even though this has a positive impact, the Secretary-General of the United Nations raised concerns that the present crisis is triggered by the consumption of fossil fuels, while the development issue concerning climate change impacts on a global scale is still facing uncertainty [129].…”
Section: Threats (T)mentioning
confidence: 99%
“…(2022) reported that the Russia-Ukraine conflict appears not to entirely change the investors' assessment of a possible acceleration of a green energy transition. Furthermore, Saktiawan et al (2022) reported that European countries have increased the budget for developing and using environmentally friendly energy to remove the dependence on gas and oil energy from Russia. Accordingly, Steffen and Patt.…”
Section: Introductionmentioning
confidence: 99%